2017
DOI: 10.1002/lary.26692
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal surgical treatment in transgender women: A systematic review and meta‐analysis

Abstract: NA Laryngoscope, 127:2596-2603, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 26 publications
0
18
0
9
Order By: Relevance
“…The third approach reduces the mass and increases the stiffness of the vocal fold 7 . The reported efficacy of each approach varies, with two recent systematic reviews concluding that no one technique was definitively superior to the others 8,9 . However, a third systematic review/meta‐analysis pointed to glottic shortening procedures as producing the largest and most reliable increase in f o 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The third approach reduces the mass and increases the stiffness of the vocal fold 7 . The reported efficacy of each approach varies, with two recent systematic reviews concluding that no one technique was definitively superior to the others 8,9 . However, a third systematic review/meta‐analysis pointed to glottic shortening procedures as producing the largest and most reliable increase in f o 10 .…”
Section: Introductionmentioning
confidence: 99%
“…We did not find any clinical trial in the literature comparing these two techniques for SVF performed by the same group. Recently, three systematic reviews analyzed the results of different techniques; Schwarz et al concluded that no evidence exists regarding which surgical technique would be better for the vocal approach of a transgender woman; Song et al concluded that vocal folds shortening procedures appear to result in the largest increase in F 0 , as suggested in our study; and Van Damme et al concluded that all of the techniques lead to a substantial rise in postoperative F 0 , but perceptually. Primarily, laryngeal web formation seems risky for decreasing voice quality …”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is not clear which SVF technique is the best. Inconsistent F 0 results increase; and duration in time, quality of life (QoL), voice quality, and self‐perceived femininity of the voice (SpFv), and so forth, have been reported …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Se descartan otros 9, por hacer referencia a intervenciones médico-quirúrgicas para el tratamiento de la voz transexual (Anderson, 2014;Casado et al, 2016;Casado, Rodríguez-Parra, & Adrián, 2017;Kim, 2017;Mastronikolis, Remacle, Biagini, Kiagiadaki, & Lawson, 2013;Schwarz, Fontanari, Schneider, et al, 2017;Song & Jiang, 2017). Finalmente, se prescinde del análisis de un artículo en finés al cual no se tiene acceso y no es posible evaluar si cumple estrictamente los criterios de inclusión (Sellman & Rihkanen, 2015).…”
Section: Metodologíaunclassified